Progress on Coastal Ecosystems: Corals and Mangroves Recovery 12 Years Later after March 2005 Earthquake in North Nias, North Sumatera. - Suyarso .; Bayu Prayuda; Praditya Avianto (Jurnal Segara, 2017)
Twelve years ago 9.3 Mw earthquake in the Andaman Islands, on December 26, 2004 accompanied by the tsunami in Aceh led to extraordinary losses, unprecedented for human life in coastal areas of Indonesia and neighboring countries. A few months later, on March 28, 2005  an earthquake 8.7 Mw has occured around Nias, hundreds of hectares of coral reef ecosystems lifted into the terrestrial, many corals die of drought and collapse due to earthquake vibration. Similarly, most of the mangrove moved away from the coastline due to land lifting. The purpose of this study is to determine the development of coastal ecosystems, especially coral reefs have been damaged by the earthquake and mangrove due to changes in the environment. The method used in this study is remote sensing technique through the data acquired from landsat imageries, measurements of coastal profile, coral reef health monitoring data collected in each year at six permanent stations. The field research conducted in August 2005, December 2014 and December 2015, the last two activities are under research collaboration between the Marine Agency of North Nias Regency and Research Center for Oceanography LIPI. The results showed in the period 2007-2010 live coral coverage is likely to increase in the range between 2.23% to 48%. Instead since 2014 showed a significant decrease in almost all stations. Twice earthquakes with 33the magnitude 8.2 Mw and  8.6 Mw occurred almost simultaneously on April 11, 2012 at 400 km southwest of Aceh is thought to play a role in tear down the developing corals. Similarly, the existence of mangrove that has moved away from the coastline due to the land lifting in 2005, species of  Rhyzophora desiccated  and died slowly but other species such as Aegiceras, Dolichandrone, Xylocarpus and Cheriops  appear stayed on  the dry land condition and seemed to be growing normally